Analysis of Vulnerability Level of Beach Abration Disaster in the District of North Galesong, Takalar Regency - Firdaus, Firdaus; Chaerul, Muhammad; Gusty, Sry (Universitas Ibn Khaldun Bogor, 2022)
Vulnerability is the inability of an individual or community group to minimize the impact caused by a hazard. Information about the level of vulnerability is essential to reduce the risks and effects caused by a disaster. Assessment of the level of vulnerability of threatened areas is carried out to minimise losses and the population exposed to disasters. This study aims to determine the level of vulnerability to coastal abrasion in North Galesong District, Takalar Regency. The analytical method used is the vulnerability index of coastal areas consisting of population components, namely population density and vulnerable groups, economic components, low-income families and anglers, physical components in the form of building density and ecological features in the form of mangrove vegetation. Analysis of vulnerability index data using the vulnerability assessment table issued by the Regulation of the Head of BNPB Number 2 of 2012. The overall results of the research are the vulnerability level of coastal villages in North Galesong District is in the high category. The category of high vulnerability is a condition of a community or society that leads to or causes a high inability to deal with the threat of coastal erosion in the North Galesong District. Vulnerability reduction activities can be carried out by increasing public understanding, especially vulnerable groups and poor fishers groups, through training and socialization activities regarding potential disaster threats, the driving factors for their occurrence and the risks. Socialization of the potential danger of abrasion and extreme waves for fishers is necessary to increase knowledge in dealing with disaster threats. Socialization can be done by inviting anglers to disaster management activities.